2005
DOI: 10.1097/01.bot.0000151814.87174.74
|View full text |Cite
|
Sign up to set email alerts
|

Unreduced Chronic Dislocation of the Humeral Head With Ipsilateral Humeral Shaft Fracture

Abstract: The purpose of reporting this case is to illustrate a treatment plan for a chronically anteriorly dislocated shoulder associated with an ipsilateral humerus fracture, a condition heretofore not addressed in the literature to our knowledge. An 18-year-old female, left hand dominant, injured her left upper extremity and liver in a motor vehicle accident. X-rays at time of injury revealed a diaphyseal facture of her left humerus. No x-rays of the shoulder were taken at time of injury. Treatment consisted of a pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“… 1 3 4) However, though it is uncommon among chronic dislocations, there have been a few cases where this ailing condition did not incite persistent pain, creating a further postponement in establishing the diagnosis. 4 5) In the case described in this paper, chronic shoulder dislocation was found in a patient after 1 year, with the affected individual experiencing little pain. This patient had not received medical treatment due to an improvement in symptoms and function shortly after an injury.…”
mentioning
confidence: 75%
See 3 more Smart Citations
“… 1 3 4) However, though it is uncommon among chronic dislocations, there have been a few cases where this ailing condition did not incite persistent pain, creating a further postponement in establishing the diagnosis. 4 5) In the case described in this paper, chronic shoulder dislocation was found in a patient after 1 year, with the affected individual experiencing little pain. This patient had not received medical treatment due to an improvement in symptoms and function shortly after an injury.…”
mentioning
confidence: 75%
“…These methods include no treatment, closed manipulation, open reduction with or without fixation and resection arthroplasty, and recent additions of arthroscopic reduction with repair of associated labral and rotator cuff injuries, and joint replacement. 1 3 5 7 8) Although reduction is relatively easy in most cases of acute shoulder dislocation, it will become nearly impossible in chronic cases to reduce a joint that has been dislocated for more than 2 weeks. One study suggested that attempts to reduce the joint should be dropped if the dislocation has been left for more than 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,10,12 To date, no reports have been published of missed posterior dislocation after intramedullary fixation of proximal humeral fractures. Cooper 2 stated in 1839 that the physical findings were so classic that it was ''an accident which cannot be mistaken.''…”
Section: Discussionmentioning
confidence: 99%